Synthesis and characterization of novel 1,6-dihydropyrimidine derivatives for their pharmacological properties - Basavaraj Padmashali, Ballekere Nanjundaswamy Chidananda, Banuprakash Govindappa, Siddesh M. Basavaraj, Sandeep Chandrashekharappa, Katharigatta N. Venugopala & (Journal of Applied Pharmaceutical Science, 2019)
The present research work involves the use of commercially available thiophene-2-carbaldehyde as a starting material to construct novel pyrimidine compounds. Synthesis of pyrimidine derivatives has been done by the trimolecular Biginelli condensation reaction, which involves the use of thiophene-2-carbaldehyde with cyano ethylacetate and thiourea to yield 4-oxo-6-(thiophen-2-yl)-2-thioxo-1,2,3,4-tetrahydropyrimidine-5-carbonitrile (1). The intermediate 1 was methylated using methyl iodide and K2CO3 in dimethylformamide (DMF) which afforded dimethylated derivative 1-methyl-2-(methylthio)-6-oxo-4-(thiophen-2-yl)-1,6-dihydropyrimidine-5-carbonitrile (2). The intermediate compound 2 when refluxed with hydrazine hydrate in ethanol as a solvent led to the formation of the parent compound 2-hydrazineyl-1-methyl-6-oxo-4-(thiophen-2-yl)-1,6-dihydropyrimidine-5-carbonitrile (3), the parent compound 3 was used for the synthesis of carboxamides of N′-(5-cyano-1-methyl-6-oxo-4-(thiophen-2-yl)-1,6-dihydropyrimidin- 2-yl)substituted benzohydrazide (4a–d) and Schiff bases of (E)-2-(2-substituted benzylidenehydrazineyl)-1-methyl- 6-oxo-4-(thiophen-2-yl)-1,6-dihydropyrimidine-5-carbonitrile (5a–g). Selected title compounds are screened for antibacterial, analgesic, and antifungal activities.
Keywords: Substituted 1,6-dihydropyrimidine, synthesis, antibacterial, antifungal, analgesic.